Zoning Determination Analysis of New Student Admissions Using N-Dimensional Euclidean Distance - Satrio Muhammad Alif; Nisya Kartika; Andri Hernandi (Jurnal Pendidikan Geografi Gea, 2022)
The zoning is one of the ways in the New Student Admissions (PPDB) system in Bandar Lampung City. The implementation of PPDB has shortcomings such as lack of capacity and unequal public high schools in the city of Bandar Lampung. Diverse topography makes zoning determination in Bandar Lampung City requires elevation. This study aims to determine the zone of PPDB of Public High School (SMAN) in Bandar Lampung City using Euclidean N-dimensional Distance to get the lack of capacity of each SMAN. This research is a quantitative research using descriptive research method with a sample of the assumption point of residence (APR) in the city of Bandar Lampung which has an interval of 10 meters. Each APR is used in calculating the distance to each SMAN to obtain SMAN zoning with the principle of minimum three-dimensional distance. The population of each zone is calculated from the proportion of the zone in each district and the population of each sub-district involved. The population is linked with the capacity of the school to get information on the lack of capacity of each SMAN. Zone 6, which contains SMAN 6, is the widest zone in the city of Bandar Lampung. There is no SMAN that is not lacking in capacity with the scenario that 75% of the population continues to high school. The districts that most need to increase their capacity are Kedaton, Way Halim, Sukabumi Panjang, Enggal, and Tanjung Karang Pusat districts.